Improving critical care competencies of nurses through simulation: A study at upper east regional hospital, Ghana - Eric Abugre; Francis K Wuni; Anita Ohenewa Yawson; Paschalina Anupio Ayirezang (International Journal of Africa Nursing Sciences)
Background: Intensive care nursing is focused on severely ill patients who benefit from the attention of competent and skilled personnel. The purpose of this study was to use simulation to enhance the critical care skills of nurses working in the intensive care unit at the Upper East Regional Hospital in Ghana. Method: A cross-sectional study design was used, the primary objective was to evaluate, and potentially enhance the critical care competencies of general nurses working in the intensive Care Unit (ICU). The study participants were purposively selected, and were specifically involved in a participatory clinical simulation exercise. To evaluate and gather the data, a low-fidelity manikin simulation aided by a checklist and paper-based, researcher-administered questionnaire was employed. To gather the necessary and representative sample for the investigation, Yamane’s sample size formula was utilized to select 19 participants for the study. The data collection last for one month, the first two weeks for the pre-training exercise and the last two weeks for post evaluation, however data collection lasted for a month. Results: The findings of the study indicate that the simulation conducted for the nurses improved their CPR, communication, and drug administration competencies. Their competency score ranged between “competent” and “outstanding” after the training. Generally, the findings of the current study indicate that the ICU nurses demonstrated excellent and acceptable skillsets for delivering their services at the ICU. This reflected their good communication skills towards their colleagues, clinicians, patients, and patients’ relatives. Conclusion: Though the nurses had poor competency in performing CPR and administering essential medicines in the ICU, training interventions significantly improved their competencies.